Pelatihan Kader Sehat Jantung dan Jiwa - Ibrahim, Sri Andriani; Antu, Mihrawaty S; Daud, Serly (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2023)
The training program for healthy heart and soul cadres in handling anxiety for hypertension sufferers aims to train cadres to provide knowledge and skills in recognizing signs of anxiety in hypertension sufferers and providing appropriate treatment to reduce the negative impact on health. Mentoring healthy heart and soul cadres aims to empower cadres who have taken the form of efforts to handle anxiety levels in hypertension sufferers. Cadre assistance is able to increase cadres' knowledge and skills in handling anxiety after an anxiety screening is carried out so that the level of anxiety can be known so that treatment can be carried out. Keywords: Cadres, Healthy Heart and Soul, Training